FAKTOR YANG BERHUBUNGAN DENGAN AKURASI LABEL TRIASE INTRARUMAH SAKIT DI INDONESIA: TINJAUAN LITERATUR - Sanjana, I Wayan Edi; Widyandari, Ni Made Ayu Sukma; Megayanti, Sri Dewi; Agustini, Ni Luh Putu Inca Buntari (Coping: Community of Publishing in Nursing; Vol 11 No 5 (2023): Oktober 2023DO - 10.24843/coping.2023.v11.i05.p01, 2023)
Emergency Department (ED) is the main gateway for patient care in hospitals. Health workers who meet the patient for the first time have the task of categorizing the patient's emergency condition known as triage. Triage has a different mechanism according to the conditions found. If the triage label given to the patient is not appropriate, it will result in a lack of optimal service in the ED. Health workers who perform triage should have knowledge in determining the accuracy of patient labelling. This study aims to summarize the factors related to the accuracy of triage labelling in Indonesia. This research is a literature review on several data bases including Science Direct, Proquest, and Google Scholar. Articles are searched with several keywords in Indonesian and English combined with Boolean. Article is selected according to the research objectives. The results showed a total of 1012 article from the three databases which were then selected 11 articles for analysis. Factors related to the accuracy of the triage label are classified into two, namely internal and external factors. Internal factors include characteristics (age, work experience, emergency training experience), knowledge, attitudes, skills and motivation of health workers. External factors include overcrowded ED conditions, facilities and infrastructure, human resources, the flow of patients entering the ED. Knowledge is the most frequently found factor related to the accuracy of the patient's triage label. Continuous training is needed to increase knowledge of triage label accuracy.